How Important Are Banks for Development? National Banks in the United States, 1870–1900 - Fulford, Scott L. (The Review of Economics and Statistics, 2015)
Do banks matter for growth, and if so, how? This paper examines the effects of national banks in the United States from 1870 to 1900. I use the discontinuity in entry caused by a large minimum size requirement to identify the effects of banking. For the counties on the margin between getting a bank and not, gaining a bank increased production per person by 10%. National banks in rural areas improved agriculture over manufacturing, moving counties toward geographic comparative advantage. Since these banks made few long-term loans, the evidence suggests that the provision of working capital and liquidity matters for growth.